Doped sol–gel films vs. powders TiO2: On the positive effect induced by the presence of a substrate. Issue 1 (March 2016) - Léonard, Géraldine L.-M.; Malengreaux, Charline M.; Mélotte, Quentin; Lambert, Stéphanie D.; Bruneel, Els; Van Driessche, Isabel; Heinrichs, Benoît
Graphical abstract: Highlights: Substrate changes the mobility of species during calcination. Powders: dopants disturb the crystallinity and so the photocatalytic activity. Films: dopants increase the photoactivity and superhydrophilicity. Silver nanoparticles act as an electron trap. Carbon contamination can be remove by powered UV light. Abstract: SiO2 and Ag–SiO2 doped TiO2 films and powders have been produced using a controlled sol–gel process. The dopant has been introduced using an alkoxysilane-functionalized ligand, with or without complexed silver ions. The influence of dopants on physico-chemical properties of the catalysts is studied by XRD, TEM–EDX, DRUV–vis analyses in the case of powders, while GIXRD, XPS, profilometry, UV–vis absorption analyses have been used for thin films. The photocatalytic activity has been evaluated from the degradation of methylene blue under UV-A light in the presence of the different catalysts over a period of 24 h. The detailed comparison between powders and films highlights a surprising positive effect in the case of films due to the presence of the substrate. In the case of photocatalytic powders, the presence of SiO2 or Ag–SiO2 into the TiO2 matrix has a detrimental effect on the photocatalytic activity while the opposite tendency is observed in the case of films, with best activities obtained with Ag–SiO2 doping. Different factors, in particular crystallinity modification between powders and films, have been studied to explain these opposite behaviors. In the case of powders, crystallization is hindered by SiO2 and Ag particles incorporation into the TiO2 matrix, leading to a decrease of the photocatalytic activity. In the case of thin films, probably because of the presence of a substrate, crystallization is not influenced by the presence of SiO2 and Ag particles. Therefore, the latter ones can fully play their role of electron traps leading to an enhanced photocatalytic activity.